Health Care Scenario in India and its Economic Impact - Singh, Kawaljot (Thapar Institute of Engineering & Technology, Patiala, 2019)
Healthcare is the maintenance of health with the help of illness prevention, diagnostic, and physical and mental impairments in people. Basically, the present study is on Indian health care system. How is the infrastructure of hospitals, dispensers, and other government or private clinics or labs? Health care system are organization established to meet the health needs of targeted populations. Primary and secondary sectors are there in Indian health care system. In past few years health care rates of the India is higher with birth rate is increases and mortality rate is decreases. Government used schemes like Lifeline Jeevan-rekha express was in 1991. The lifeline express was run by the government to provide a medical, on the spot diagnostic and curative interventions for disabled adults and children.Healthcare standard in India is a major concern for the government of India, as the quality of healthcare services is very poor in India. There is shortage of qualified healthcare professional moreover even the medicines are not available sometimes. The present study is aimed at examining the gender and education based opinion and experience of the people of India regarding the level of healthcare services in India. For this purpose a survey based analysis is done in the present study, which was answered by 70 individuals, consisting 29 males and 41 females, and for the education based analysis 11 Under Graduates, 27 Graduates, 24 Post Graduates and 8 with education higher than PG. The study is also aimed at studying the mortality rates and HDI index across various states of India. Major findings of the study are that -Life Expectancy is 66.9 for Females and 63.9 for males in India, while it is 86.1 for females and 78.9 for Males in Japan. Thus India has to improve in terms of Health indicators. Total Fertility Rate (TFR) is highest in Pakistan, followed by Nepal and then is India. TFR for India is also quite high. Regression results for Quality of healthcare and Healthcare cost highlight an inverse relation between the two. An increase in healthcare cost improved the healthcare quality. Hence, there is a need to spend more on healthcare expenditure.
Keywords: Healthcare; Mortality Rate; Human Development Index; Economic Impact; India